PERANCANGAN SISTEM INFORMASI PENJUALAN WATCHES MENGGUNAKAN MICROSOFT VISUAL BASIC .NET DI PT. GILANG AGUNG PERSADA GUESS BOUTIQUE TSM BANDUNG - Yudhi Yanuar; Nurhapipah (POLITEKNIK PIKSI GANESHA, 2019)
This research aim to describe the watches sales system design using Microsoft Visual Basic.Net and Microsoft Access at PT Gilang Agung Persada Bandung. The method used in this research is waterfall method. Data collection techniques are performed with observation, interviews, and literature review relating to the subject matter.Sales system in this company is not computerized so make that system not effective andefficient. Therefore the necessary computer based data collection with better applications, because this sales system have an important function that make all the work system is easy, fast, and accurately.In order to make this sales system, the writer used UML (Unified Modelling Language)methods and implemented with Microsoft Visual basic .Net programing language also the Microsoft Access as a DBMS (Data Managemen System). With the existence of this application is expected of sales system can produces data effectively and accurately.